Disaster Resilience in Residential Area (Case Study: Siau Islands District Tagulandang Biaro, North Sulawesi Province Post Space Mountain Eruption in 2024) - Dewi, Naufa Gutta; Kurniawan, Naufal Irhab; Wijaya, Arya Tri; Anggani, Nirma Lila (Amcolabora, 2025)
Indonesia, located on the Pacific Ring of Fire, has a high potential for volcanic disaster due to tectonic plate subduction. The eruption of Mount Ruang on April 16 2024 in the Siau Islands District of Tagulandang Biaro (Sitaro), North Sulawesi Province, resulted in a significant impact on the local community with 9,083 people and 5,000 houses affected. This research aims to understand the factors that influence community resilience in facing natural disasters, especially volcanic eruptions, as well as identify weaknesses and strengths in existing resilience systems. The method used is qualitative with secondary data analysis from BNPB and PVMBG. The research results show the need for volcanic emergency training, building disaster-resistant infrastructure, strengthening early warning systems, relocating residents, and increasing coordination between institutions. Mitigation efforts by the North Sulawesi Provincial government and BPBD, including evacuation and restoration of learning activities, are expected to increase community resilience to future volcanic disasters and minimize their impact.